Development of an isothermal recombinase polymerase amplification assay for rapid detection of pseudorabies virus. (June 2017) - Yang, Yang; Qin, Xiaodong; Zhang, Wei; Li, Zhiyong; Zhang, Shuaijun; Li, Yanmin; Zhang, Zhidong
Abstract: Recombinase polymerase amplification assays using real-time fluorescent detection (real-time RPA assay) and lateral flow dipstick (RPA LFD assay) were developed targeting the gD gene of pseudorabies virus (PRV). Both assays were performed at 39 °C within 20 min. The sensitivity of the real-time RPA assay and the RPA LFD assay was 100 copies per reaction and 160 copies per reaction, respectively. Both assays did not detect DNAs from other virus or PRV negative samples. Therefore, the developed RPA assays provide a rapid, simple, sensitive and specific alternative tool for detection of PRV. Highlights: PRV real-time RPA assay was developed first time to detect PRV. PRV RPA LFD assay was developed first time to detect PRV. The RPA assay provides a rapid, sensitive and specific alternative for detection of PRV.